Botanical Composition and Diversity of Forage for Swamp Buffalo in Natural Pasture in Tandung Village, Tinambung District, Polewali Mandar Regency - Andi Sukma Indah; Hajar Hajar; Ikram Fajrul Ramli; Hamsa Hamsa; Muh. Wali Sangadi; Sarpilah; Muhammad Fadli (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
This study aimed to identify the types of forage and determine the botanical composition and diversity of forage in swampland as a natural pasture in Polewali Mandar, West Sulawesi, Indonesia. The measurement and sampling of forage and the measurement of botanical composition and diversity were conducted using a non-probability approach, specifically purposive sampling. Sampling was carried out using quadrants spread out, which were thrown 50 times using the dry weight rank method. The forage identified on natural pastures in Tandung Village, Tinambung District, Polewali Mandar Regency is 15 forage species, including six grasses, three legumes, and six weeds. Based on the analysis of botanical composition, forages with the highest SDR values were Spartina anglica, Agrortis stolonifera, and Cyperus rotundus. The Shannon-Wiener diversity index (H′) was 2.29, with a medium category, Shimpson's index (C) had a value of 0.12, with a category of no dominating species, the evenness of species (E) was 0.84, with a stable category, and the species richness index (Dmg) was 1.37, with a medium-low category.